1994
DOI: 10.1093/jnci/86.15.1140
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p160erbB-3 and p185erbB-2 in Prostatic Intraepithelial Neoplasia and Prostatic Adenocarcinoma

Abstract: These results suggest that increased expression and changes in the subcellular distribution of both p160erbB-3 and p185erbB-2 represent early events in the development and progression of prostatic adenocarcinomas. The high expression and distribution of both p160erbB-3 and p185erbB-2 are retained both in advanced-stage primary and metastatic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 0 publications
7
78
2
2
Order By: Relevance
“…26,33 Moderate-tostrong immunoreactivity for HER-2/neu was detected in 27 of 29 localized adenocarcinomas (93%) and in 15 of 16 metastatic prostatic adenocarcinomas (94%). 12 Cohen et al noted expression of HER-2/neu in 7 of 23 patients with organ-confined prostate carcinoma and in 9 of 44 samples from metastatic deposits, resulting in an overall expression rate of 24%. 27 Sadasivan et al found that 9 of 25 prostate carcinoma samples (36%) showed HER-2/neu overexpression, and such overexpression was correlated with tumor grade, stage, and high S-phase and DNA aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…26,33 Moderate-tostrong immunoreactivity for HER-2/neu was detected in 27 of 29 localized adenocarcinomas (93%) and in 15 of 16 metastatic prostatic adenocarcinomas (94%). 12 Cohen et al noted expression of HER-2/neu in 7 of 23 patients with organ-confined prostate carcinoma and in 9 of 44 samples from metastatic deposits, resulting in an overall expression rate of 24%. 27 Sadasivan et al found that 9 of 25 prostate carcinoma samples (36%) showed HER-2/neu overexpression, and such overexpression was correlated with tumor grade, stage, and high S-phase and DNA aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…[248][249][250] Furthermore, ERBB2/ERBB3 complexes caused AKT-independent phosphorylation of the androgen receptor that stabilized the protein and enhanced its transcriptional activity. 248 Increased expression of ERBB3 in prostate cancers, compared with normal prostate, has been demonstrated by immunohistochemistry in several studies 79,[251][252][253][254] and was associated with poor prognosis. 252 Microarray analyses have likewise shown an increase in ERBB3 mRNA in these cancers.…”
Section: Prostate Cancermentioning
confidence: 99%
“…113 A member of the CIP/KIP family of cyclin-dependent kinase inhibitory proteins, p27KIP1, also showed significant reduction in expression in PIN, cancer, and metastatic cancer when compared with benign prostatic epithelium. 114 Other markers show progressive increase, including including human glandular kallikrein 2 (hK2), 115 c-erbB-2 (Her-2/neu) and c-erbB-3 oncoproteins, 108,116 c-met proto-oncogene, 41 bcl-2 oncoprotein, 117,118 mutator (RER( þ )) phenotype, 104 epidermal growth factor and epidermal growth factor receptor, 108,119 type IV Collagenase, Lewis Y antigen, TGF-alpha, apoptotic bodies, 71,73,104 mitotic figures, 71 PCNA expression, Ki-67 expression, MIB-1 expression, 111 tenascin-C, 120 aneuploidy and genetic abnormalities, 62,111,121-127 microvessel density, Ep-Cam transmembrane glycoprotein, 128 Insulin-like growth factor binding protein IGFBP-rP1, and p53 mutations, 129 although one group found no p53 expression immunohistochemically in PIN. 130 Prostate-specific membrane antigen, an abundant transmembrane glycoprotein, shows increased expression in PIN and cancer when compared with benign epithelium, 131,132 and this expression was unaffected by short-term androgen deprivation therapy.…”
Section: Genetic and Molecular Changesmentioning
confidence: 99%